2018
DOI: 10.3390/polym10090934
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Fluorine Substituents on Iminopyridine Fe(II)- and Co(II)-Catalyzed Isoprene Polymerization

Abstract: A series of iminopyridine complexes of Fe(II) and Co(II) complexes bearing fluorinated aryl substituents were synthesized for the polymerization of isoprene. The structures of complexes 3a, 2b and 3b were determined by X-ray diffraction analysis. Complex 3a contained two iminopyridine ligands coordinated to the iron metal center forming an octahedral geometry, whereas 2b adopted a chloro-bridged dimer, and 3b featured with two patterns of cobalt centers bridged via chlorine atoms. Complexes 2b and 3b represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…A reversal of the selectivity was achieved by modifying the nature of the substituent on the imino group, the N -aryl group (aryl = supermesityl) favoring the cis -1,4-selectivity while the trans- 1,4-selectivity was promoted with an N -alkyl substituent (alkyl = tert-octyl). On the other hand, the same sets of complexes were independently evaluated for the polymerization of isoprene by the group of Chen [25] and the group of Wang [26] in the presence of MAO. Surprisingly, the system bearing N -alkyl substituent afforded opposite microstructures, respectively, whereas the complex with N -aryl group exhibited a slight cis -1,4 selectivity with a moderate amount of 3,4 units, relatively, similar to that found upon activation with trialkyl aluminum and [Ph 3 C][B(C 6 F 5 ) 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reversal of the selectivity was achieved by modifying the nature of the substituent on the imino group, the N -aryl group (aryl = supermesityl) favoring the cis -1,4-selectivity while the trans- 1,4-selectivity was promoted with an N -alkyl substituent (alkyl = tert-octyl). On the other hand, the same sets of complexes were independently evaluated for the polymerization of isoprene by the group of Chen [25] and the group of Wang [26] in the presence of MAO. Surprisingly, the system bearing N -alkyl substituent afforded opposite microstructures, respectively, whereas the complex with N -aryl group exhibited a slight cis -1,4 selectivity with a moderate amount of 3,4 units, relatively, similar to that found upon activation with trialkyl aluminum and [Ph 3 C][B(C 6 F 5 ) 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for the same catalytic systems and under the same experimental conditions, different activities were found by these two research groups, enabling almost complete conversion of the isoprene in one case, while in the other, only 10 to 20% conversion was reached. In addition, Wang studied the polymerization of isoprene with aldiminopyridyl iron-based system bearing fluorinated N -aryl substituent (Figure 2(B)) [26], which was activated either by MAO alone or by a combination of MAO and [Ph 3 C][B(C 6 F 5 ) 4 ]. The obtained polyisoprene exhibited an equal content mixture of cis -1,4 and 3,4 units for the former while high trans -1,4 selectivity (>95%) was found in the presence of MAO/[Ph 3 C][B(C 6 F 5 ) 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, rare-earth metal and titanium catalysts afforded cis -1,4 or trans -1,4 polyisoprene with up to 98% selectivity [11,12,13,14,15]. In addition, some late transition-metal catalysts were also studied for isoprene polymerization, such as well-defined Fe and Co complexes [16,17,18,19,20,21,22,23]. However, the polymerization of isoprene with mid-transition metal-based catalysts remains less explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that iminopyridine ligands are widely studied for many catalytic reactions, due to their facile synthesis and easy to control the catalytic performance by means of different substituents [19,20,21,23]. To extend this study, herein, we reported the synthesis of a series of iminopyridine vanadium(III) complexes and employed as catalysts for isoprene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Ni(II) complexes with Schiff base ligands were employed that showed high catalytic activity when using methylaluminoxane as co-catalyst. The effect of ligand structure on the behavior in coordination polymerization of isoprene was studied in depth by Wang and coworkers [39]. More specifically, poly(isoprene) was synthesized with Fe(II) and Co(II)-derived catalyst complexes based on iminopyridine ligands.…”
mentioning
confidence: 99%